Kontribusi Ibn Hazm Terhadap Pembaharuan Hukum Islam: Upaya Pemurnian Hukum Islam dari Dominasi Ra'y - Isnatin Ulfah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2006)
This study aims to analyze Ibn Hazm's contribution to the renewal of Islamic law, especially in his efforts to purify Islamic law from the domination of ra'y (rational opinion). As the main figure of the Zahiri school of thought, Ibn Hazm rejected the use of qiyas, istihsan, and taqlid, and emphasized a literal understanding of the law based on the text of the Qur'an and Hadith. This study uses a qualitative method with a literature study approach, analyzing Ibn Hazm's works such as Al-Muhalla and Ihkam fi Ushul al-Ahkam. The results show that Ibn Hazm contributed to offering a more textualist approach to Islamic law, which rejects subjectivity in ijtihad. Although his approach is often criticized for being rigid, his thoughts continue to have an influence in the discourse of modern Islamic law, especially in the effort to maintain the purity of shar'i arguments.